Three Types of Broadly Reacting Antibodies against Influenza B Viruses Induced by Vaccination with Seasonal Influenza Viruses. (8th May 2018) - Hirano, Daisuke; Ohshima, Nobuko; Kubota-Koketsu, Ritsuko; Yamasaki, Ayami; Kurosawa, Gene; Okuno, Yoshinobu; Yoshida, Shunji; Kurosawa, Yoshikazu
Abstract : We analyzed the antibody (Ab) repertoire against influenza B viruses induced by vaccination with seasonal influenza viruses in one individual who had never been vaccinated until 2009. The vaccine used in this study comprised B/Massachusetts/2/2012 (Yamagata lineage), A/Texas/50/2012 (H3N2), and A/California/7/2009 (H1N1). One month after the subject received two vaccinations, blood (200 ml) was obtained and peripheral mononuclear cells were prepared, and a large Ab library was constructed using phage display technology. The library was screened with HA-enriched fraction of B/Massachusetts/2/2012 and B/Brisbane/60/2008 (Victoria lineage) virus, and a total of 26 Abs that potentially bound to hemagglutinin (HA) molecules were isolated. Their binding activities to six influenza B viruses, three of Yamagata lineage and three of Victoria lineage, and two influenza A viruses, H1N1 and H3N2, were examined. The Abs showed cross-reactivity at three different levels. The first type bound to all Yamagata lineage viruses. The second type bound to both Yamagata and Victoria lineage viruses. The third type bound to both influenza A and B viruses. These results indicate that common epitopes exist on HA molecules of influenza virus at various levels, and humans have capability to produce Abs that bind to such common epitopes.